Efeitos de inserção do íon de cobre na matriz cristalina do Bi12GeO20 : estudo de primeiros princípios - Lima, Jailsson Silva (2018)
In this dissertation the effects of insertion of the Cu ion into the Bi12GeO20 (BGO) crystalline matrix were studied by means of the first-order computational techniques based on the density functional theory. The FP-LAPW method implemented in the WIEN2K code was applied. Correlation and exchange effects were treated with the GGA-PBE functional (for structural optimization) and with the TB-mbj potential (for the calculation of the electronic properties). Within the BGO crystalline matrix there are two possible accommodation sites of the impurity, Ge4+ and Bi3+. Experimental studies have shown that most of the transition metal impurities prefer to accommodate at the Ge4+ site. This is surprising, since the impurities are expected to replace the Bi3+ site because it has the more compatible charge state and the larger ionic radius. On the other hand, the Cu ion is one of the few that has a preference for the Bi3+ site. It accommodates at this site with an electronic configuration 3d9 and with oxidation state 2+. In order to understand these facts, not yet explained by the experiments, two distinct systems were simulated: (1) the BGO crystal with Cu impurity at the Ge4+ site, and (2) the BGO crystal with Cu impurity at the Bi3+ site. The defect was studied in the neutral, positively and negatively charged state. The insertion preference was estimated from the calculations of the defect formation energy. Electronic properties were also calculated and the quantum theory of atoms in molecules was applied to estimate the oxidation state of Cu. The results confirmed the preference of accommodation of the Cu ion at the Bi3+ site, in accordance with the results obtained by experimental techniques such as EPR. The electron structure analysis showed that the Cu valence is 2+ (3d9) regardless of the charge state. The changes of the structural, electronic and magnetic properties of the BGO compound in the presence of Cu impurity at both sites of the incorporation were analysed and clarified.